LEGAL POLITIC OF THE FORMATION OF INDONESIAN NATIONAL CRIMINAL CODE (KUHP) - Simon Nahak (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2018)
Abstract Legal politic is a policy of legislation through the stages of formulation/formulation that is the drafting of a regulation both the rules in general and the special rules of criminal by the legislator in this case the legislator with the Government. The errors or weaknesses of the legislative policy are part of a strategic error that can be an obstacle to prevention and crime prevention at the Judicative and Execution stage. The political formation of the future Penal Code does not only deal with the substance of law, the legal structure but rather focuses on the legal culture based on Pancasila as the basis of the State. Renewal of criminal law is more directed to actions in the form of a series of prohibited acts, criminal/false responsibility and punishment system. The method used is mix method consisting of Juridical-Normative legal writing method and collaboration of Juridical-Empirical. The results of this study are the politics of the formation of the National Criminal Code, referring to the Neo-Classical School thought that maintains a balance between the objective (Actus Reus) and Subjective (person/soul/mind/Mens rea) and actually the form of Political law is Unification and codification of law, Supremacy of law, Renewal of national law, Eliminating legal dualism, Increasing legal awareness and legal culture, Firm enforcement is firm, consistent, and non-discriminatory. Keywords: Legal Politic, KUHP, Constitution of the State of the Republic of Indonesia of 1945